Cedrol from ginger alleviates rheumatoid arthritis through dynamic regulation of intestinal microenvironment. Issue 22 (31st October 2022) - Zhang, Yumeng; Liu, Yang; Peng, Fei; Wei, Xinrui; Hao, Huiqin; Li, Wei; Zhao, Yuqing
Abstract : The imbalance of intestinal flora would induce immune inflammation. Abstract : The imbalance of intestinal flora would induce immune inflammation. Cedrol (CE), found from ginger by our group earlier, has been proven to play an excellent role in ameliorating rheumatoid arthritis (RA) via acting on JAK3, MAPK, and NF-κB. However, there have been no studies on CE ameliorating RA through the regulation of the micro-environment. In this study, the adjuvant arthritis model (AIA) is established to evaluate the weight, arthritis score, paw swelling, bone destruction, immune organ index, inflammatory cell infiltration, cartilage erosion, and metabolic enzymes of kidneys in AIA rats after CE intervention. The results indicated CE could alleviate paw swelling, reduce arthritis score, decrease the secretion of TNF- α, IL-6, and IL-1 β in serum in a dose-dependent manner, and inhibit the immune organ index of the spleen while having no significant effect on metabolic enzymes of the kidney. In addition, pathological sections of ankle and knee joints suggested CE might significantly prevent inflammatory cell infiltration, synovial hyperplasia, and joint degeneration and protect articular cartilage. Then, for the first time, 16S rRNA gene was applied to analyze the regulatory effect of CE on intestinal flora. CE could effectively improve the uniformity, diversity, and richness of intestinal flora, reduce the number of pathogenic bacteria, and increase the proportion of beneficial bacteria, and it significantly inhibited the abundance of Prevotella in RA rats, which was 12.43 times smaller than that in methotrexate. The distribution and excretion of CE in vivo were detected by GC-MS. It was found that CE would massively accumulate in the gastrointestinal tract after oral administration, which is then mainly excreted through feces. Interestingly, the research suggested that CE, which plays a role in the dynamic regulation of the intestinal micro-environment, could be used as a potential component to prevent RA.